PENGARUH TINGKAT PENDIDIKAN, STATUS PEKERJAAN, JUMLAH ANGGOTA KELUARGA TERHADAP PENDAPATAN KELUARGA DAN KONSUMSI PENERIMA BANTUAN LANGSUNG TUNAI DANA DESA DI KABUPATEN KLUNGKUNG - Yasa, I Gusti Wayan Murjana; Wijaya, I Wayan Tommy Sastra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 9 (2024): Vol.13.No.9. SEPTEMBER 2024 [634-685]DO - 10.24843/EEP.2024.v13.i09.p04, 2025)
The Covid-19 pandemic has impacted not only health but also social and economic aspects. The Direct Cash Assistance from the Village Fund in Klungkung Regency is expected to maintain the purchasing power of affected communities. This research aims to identify the influence of education level, employment status, and family size on the income and consumption of the families receiving the aid. A quantitative associative research method was conducted in urban and rural districts of Klungkung, with a sample size of 100 individuals. Path analysis indicates that education level, employment status, and family size have a positive and significant impact on the income of recipient families. Subsequently, income serves as a mediating factor in influencing consumption. Keyword : Education Level, Employment Status, Number of Family Members, Income, Consumption, Direct Cash Assistance to Village Funds